Elevated serum soluble endoglin (sCD105) decreased during extracorporeal elimination therapy for familial hypercholesterolemia - Blaha, Milan; Cermanova, Melanie; Blaha, Vladimir; Jarolim, Petr; Andrys, Ctirad; Blazek, Martin; Maly, Jaroslav; Smolej, Lukas; Zajic, Jiri; Masin, Vladimir; Zimova, Renata; Rehacek, Vit (Atherosclerosis, 2008)
Extracorporeal elimination is a method of LDL-lowering therapy that is used in severe familial hypercholesterolemia (FH) after other therapeutic approaches have failed. There are currently no universally accepted biomarkers that would allow determining necessary intensity of therapy and frequency of future therapeutic interventions. An ideal tool for immediate evaluation would be a readily measurable serum marker. We hypothesized that soluble endoglin (sCD105), a recently described indicator of endothelial dysfunction, may represent such a tool. Eleven patients with FH (three homozygous, eight heterozygous; Fredrickson type IIa, IIb) that have been monitored for 4.5+/-2.8 years were treated; eight by LDL-apheresis and three by hemorheopheresis. 40 sCD105 measurements were done, before and after two consecutive elimination procedures. Baseline serum sCD105 levels were significantly higher in the patients (5.74+/-1.47 microg/l in series I, 6.85+/-1.85 microg/l in series II) than in the control group (3.85+/-1.25 microg/l). They decreased to normal after LDL-elimination (p=0.0003) in all except for one patient. This return to normal was not due to a non-specific capture of endoglin in adsorption or filtration columns as demonstrated by measurement of sCD105 before and after passage through the elimination media. We conclude that the soluble endoglin levels in patients with severe FH remain elevated despite long-term intensive therapy and that they decrease after extracorporeal elimination. Endoglin can therefore serve as a marker for evaluation of the treatment efficacy and of the decreased atherosclerotic activity in patients with FH treated by extracorporeal LDL-cholesterol elimination.
Keywords: Endoglin; dospělí; endoglin; Blood Component Removal; Female; biologické markery; LDL-cholesterol; Biomarkers; Adult; výsledek terapie; ženské pohlaví; CD antigeny; Cholesterol, LDL; lidé; Hyperlipoproteinemia Type II; hyperlipoproteinemie typ II; Solubility; Treatment Outcome; rozpustnost; stupeň závažnosti nemoci; Antigens, CD; Male; separace krevních složek; receptory buněčného povrchu; Receptors, Cell Surface; lidé středního věku; mužské pohlaví; Severity of Illness Index; Middle Aged; Humans